Phosphorus and potassium balance in a corn-soybean rotation under no-till and chiseling - Calonego, Juliano Carlos [UNESP]; Rosolem, Ciro Antonio [UNESP] (Springer Nature, 2013)
Nutrient use efficiency has become an important issue in agriculture, and crop rotations with deep vigorous rooted cover crops under no till may be an important tool in increasing nutrient conservation in agricultural systems. Ruzigrass (Brachiaria ruziziensis) has a vigorous, deep root system and may be effective in cycling P and K. The balance of P and K in cropping systems with crop rotations using ruzigrass, pearl millet (Pennisetum glaucum) and ruzigrass + castor bean (Ricinus communis), chiseled or not, was calculated down to 0.60 m in the soil profile for 2 years. The cash crops were corn in the first year and soybean in the second year. Crop rotations under no-till increased available P amounts in the soil-plant system from 80 to 100 %, and reduced K losses between 4 and 23 %. The benefits in nutrient balance promoted by crop rotations were higher in the second year and under without chiseling. Plant residues deposited on the soil surface in no-till systems contain considerable nutrient reserve and increase fertilizer use efficiency. However, P release from ruzigrass grown as a sole crop is not synchronized with soybean uptake rate, which may result in decreased yields. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Cover crops; Nutrient cycling; Nutrient use efficiency; Soil management; cover crop; crop rotation; fertilizer; maize; nutrient cycling; nutrient use efficiency; phosphorus; plant residue; potassium; root system; soil profile; soil surface; soybean; zero tillage; Brachiaria; Glycine max; Pennisetum glaucum; Ricinus communis; Urochloa brizantha; Zea mays